KARAKTERISTIK BALITA PENDERITA PNEUMONIA BERDASARKAN FAKTOR RISIKO DI RSUD ABDUL WAHAB SJAHRANIE SAMARINDA TAHUN 2018 - Fatimah, Nurul; Sukartini; Tandirogang, Nataniel (Sekolah Tinggi Ilmu Kesehatan Mutiara Mahakam, 2020)
Pneumonia is an acute respiratory infection that affects the lung parenchyma, which is still the leading cause of children under-five mortality throughout the world. Age 1-24 months, low birth weight, and undernourished are the risk factors for pneumonia. The purpose of this study was to determine the description of the characteristics of children under-five patients with pneumonia in Abdul Wahab Sjahranie Hospital Samarinda, based on the risk factors. This research is a descriptive observational study. The samples of this study were all the pneumonia children under-five patients who were hospitalized at Abdul Wahab Sjahranie Hospital in January-December 2018, according to the characteristics of the sample set by the researchers, which were taken by purposive sampling technique. The data used were secondary data obtained from patient medical records, taken in June 2019 at the Medical Record Installation, Abdul Wahab Sjahranie Hospital. The number of samples obtained was 42 pneumonia patients. More children suffering from pneumonia were found in age 1-24 months (78.6%), normal birth weight (61.9%), and undernourished (57.1%).